1998
DOI: 10.1016/s0960-9822(98)70090-9
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Cyclin E expression inhibits progression through endoreduplication cycles in Drosophila

Abstract: Entry into S phase of the mitotic cell cycle is normally strictly dependent on progression through the preceding M phase. In contrast, during endoreduplication, which accompanies post-mitotic cell growth in many organisms, repeated S phases occur without intervening M phases. Upon transition from mitotic to endoreduplication cycles in Drosophila embryos, expression of the mitotic cyclins A, B and B3 is terminated and Cyclin E expression is changed from a continuous into a periodic mode [1-3]. Here, we address … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
112
2
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(125 citation statements)
references
References 15 publications
10
112
2
1
Order By: Relevance
“…One example are the polytene salivary gland cells of D. melanogaster. Also in this case, cell size is correlated with ploidy, and salivary gland cells remain smaller when endoreplication is inhibited (Follette et al, 1998;Weiss et al, 1998). Here we show that ubc9.1 morphant cells with a DNA content of 8n are larger in size than 2n and 4n cells (Figure 8, G-I), suggesting a similar direct correlation between cell size and ploidy.…”
Section: Loss Of Ubc9 Leads To Compromised Mitosis and Cellular Overgsupporting
confidence: 65%
“…One example are the polytene salivary gland cells of D. melanogaster. Also in this case, cell size is correlated with ploidy, and salivary gland cells remain smaller when endoreplication is inhibited (Follette et al, 1998;Weiss et al, 1998). Here we show that ubc9.1 morphant cells with a DNA content of 8n are larger in size than 2n and 4n cells (Figure 8, G-I), suggesting a similar direct correlation between cell size and ploidy.…”
Section: Loss Of Ubc9 Leads To Compromised Mitosis and Cellular Overgsupporting
confidence: 65%
“…In fact, the trophoblastic failure caused early embryonic lethality, and cyclin E-null animals were only obtained after tetraploid complementation rescue. Previous studies in flies suggested an intimate relationship between cyclin E expression, MCM proteins and endoreduplication (Follette et al, 1998;Su and O'Farrell, 1998;Weiss et al, 1998), and cyclin E deregulation has been linked to megakaryopoiesis in mammals as well (Garcia et al, 2000). The knockout mice extend these observations, and show that cyclin E is required for endocycles, and this probably involves defective MCM loading.…”
Section: New Insights Into Cyclin E-cdk2 Function From Knockout Micesupporting
confidence: 52%
“…Drosophila and mouse trophoblasts, in which both cyclins A and B are no longer expressed, cyclin E appears to cycle as it does in mitotic cycles (Follette et al, 1998;Sauer et al, 1995). Moreover, continuous expression inhibits rereplication in Drosophila embryos (Follette et al, 1998;Weiss et al, 1998). Our results show that at least the establishment of an extra cycle can occur in the presence of cyclin E and that in fact the accumulation of cyclin E in cells in late S and G2 phases appears to directly relate to the ability to establish a re-replication cycle.…”
Section: Discussionmentioning
confidence: 99%